2003
DOI: 10.1159/000070255
|View full text |Cite
|
Sign up to set email alerts
|

Cell Volume Induced Hormone Secretion: Studies on Signal Transduction and Specificity

Abstract: Cell swelling causes an immediate secretory response in various cell types. Induced secretion possesses some unique features suggesting the involvement of a specific signal transduction pathway. The effect of 10-20 µM GdCl3, 100 µM HgCl2, 1-100 µM indomethacin and 1-20 µM nordihydroguaiaretic acid (NDGA) on cell swelling-induced hormone secretion (isosmotic 80 mM ethanol or 15-30% hyposmotic medium) from incubated rat hypothalamic paraventricular nucleus (PVN) and posterior pituitary (oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 38 publications
3
23
0
1
Order By: Relevance
“…It has already been shown that signaling pathway involved in the cell swelling-induced insulin secretion does not include extracellular Ca 2+ [2,6,7], stretch activated channels [5] 3 or prostaglandins (for review see [7]). Our present experiments demonstrate the independence of swellinginduced insulin release from the intracellular Ca 2+ and PKC as well as its resistance to noradrenaline inhibition.…”
Section: +mentioning
confidence: 99%
“…It has already been shown that signaling pathway involved in the cell swelling-induced insulin secretion does not include extracellular Ca 2+ [2,6,7], stretch activated channels [5] 3 or prostaglandins (for review see [7]). Our present experiments demonstrate the independence of swellinginduced insulin release from the intracellular Ca 2+ and PKC as well as its resistance to noradrenaline inhibition.…”
Section: +mentioning
confidence: 99%
“…Secretion of essentially all so-packaged hormones, including pituitary luteinizing hormone, follicle-stimulating hormone, adrenocorticotropic hormone, melanocyte-stimulating hormone, thyroid-stimulating hormone, prolactin (Greer et al 1983(Greer et al , 1985(Greer et al , 1990Wang et al 1989;Sato et al 1990aSato et al , 1991, β-endorphin (Back et al 2000), hypothalamic gonadotropin-releasing hormone (Inukai et al 1992), pancreatic insulin (Blackard et al 1975), and glucagon (Blackard et al 1975), is stimulated by cell swelling. Swelling-induced thyrotropin-releasing hormone (TRH) secretion from pancreatic islets (Benicky et al 1997(Benicky et al , 2000, hypothalamic structures (Kucerova & Strbak 2001;Najvirtova et al, 2003;Bacova et al 2006b) and heart (Bacova et al 2006a) was demonstrated. Nevertheless, cell swelling-induced exocytosis possesses lim-1040 R. Hafko et al ited selectivity; cells specifically engaged in water and salt regulation retain their specific response to osmotic stimuli (Najvirtova et al 2003;Bacova et al 2006a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Swelling-induced thyrotropin-releasing hormone (TRH) secretion from pancreatic islets (Benicky et al 1997(Benicky et al , 2000, hypothalamic structures (Kucerova & Strbak 2001;Najvirtova et al, 2003;Bacova et al 2006b) and heart (Bacova et al 2006a) was demonstrated. Nevertheless, cell swelling-induced exocytosis possesses lim-1040 R. Hafko et al ited selectivity; cells specifically engaged in water and salt regulation retain their specific response to osmotic stimuli (Najvirtova et al 2003;Bacova et al 2006a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular tonicity, and the associated cell volume regulation, control many molecular and cellular functions including gene expression, neuromediator and hormone release, cell proliferation, apoptosis and migration (Van der Kloot and Molgo 1994;Soroceanu et al 1999;Lang et al 2000;Najvirtova et al 2003;Rouzaire-Dubois et al 2004;Jeon et al 2006;Ernest et al 2008;Okada et al 2009). Independently of protein synthesis, the cell volume (V) is dependent on the external osmolarity and is theoretically described by the Boyle-van't Hoff law: …”
Section: Introductionmentioning
confidence: 99%